Keluarga Sakinah dalam Pandangan K.H. Hasyim Asy'ari (1871-1947 M) dan Relevansinya dengan Hukum Keluarga Islam di Indonesia: The Sakinah Family In The View of K.H. Hasyim Asy'ari (1871-1947 AD) And Its Relevance To Islamic Family Law In Indonesia - Muhammad Aziz; Abdul Aziz Harahap (ISTIDLAL, 2022)
This study aims to describe indicators of the formation of a sakinah family according to K.H. Hasyim Asy'ari and its relevance to the Compilation of Islamic Law (KHI). This qualitative research in the form of literature study uses philosophical normative. The main data source, namely the book Dhau' al-Mishbah fi Bayani Ahkam an-Nikah by K.H. Hasyim Asy'ari. Several articles in the KHI as the theory of analysis of this research. The results of the study show that there is a relevance between indicators for the formation of a sakinah family according to K.H. Hasyim Asy'ari with the construction of legal provisions in the Kompilasi Huukum Islam (KHI). First, the indicators of complying with the legal principles, requirements, and pillars of marriage that are relevant to KHI articles 4, 16, 20, and 27. It's just that the view of K.H. Hasyim in this first indicator tends to be textual. In contrast to KHI which is more contextual. Second, the recommendation indicator in choosing a life partner that is relevant to KHI Articles Articles 15, 16, 17, and 61. In this case, the criteria for the recommendation to choose a partner by K.H. Hasyim is more detailed covering various aspects, including religion, physical, lineage, economy, psychological and social status. Third, the indicator understands the principles of the purpose and benefits of marriage that are relevant to Articles 2 and 3. Third, the indicator is to build a good partnership in carrying out the rights and obligations of husband and wife that are relevant to the KHI Article 80. However, regarding the duties or obligations of the wife, K.H. Hasyim is more detailed than KHI. The theoretical implications of this research show indicators of the formation of a sakinah family in the view of K.H. Hasyim Asy'ari has relevance as well as can be the basis for formulas in the development and renewal of Islamic marriage law in Indonesia. The limitation of this research is that it has not studied in depth the heurmenetic aspects of the construction of the views of K.H. Hasyim is related to four indicators of the formation of a sakinah family.